On the number of SRB measures for Surface Endomorphisms - Balagafsheh, Pouya Mehdipour (2014)
Let f be a C2 local diffeomorphism, of a closed surface M without zero Lyapunov exponents. We have proved that the number of ergodic hyperbolic measures of f with SRB property is less than equal to the number of homoclinic equivalence classes. We use an adaptation of Katok closing lemma for endomorphisms and prove ergodic criterion, introduced in [HHTU], for endomorphisms. We also prove some folklore results on uniqueness of SRB measures, in the presence of topological transitivity